A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

A high-performance direct biomass fuel cell utilizing red bean shell as fuel - Guangkai Lu; Boyuan Liu; Liling Long; Yundong Qian; Xiaoyuan Zeng; Senran Hao; Weizi Cai; Jie Xiao (Fuel, 2026)

Effects of innovative dry-blanching on moisture, cell wall structure, physicochemical properties and volatile compounds of microwave infrared coupled dried ginger (Zingiber officinale roscoe) - Shiyu Zeng; Bingzheng Li; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Chemistry, 2025)

Cucurbit[6]uril-heteropoly acids self-assemblies for adsorption and photocatalytic synergistic removal of diquat and paraquat in water - Liling Zeng; Xianyan Ao; Manli Xu; Yunqian Zhang; Zhu Tao (Journal of Water Process Engineering, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

Correlation between urinary rare earth elements and liver function in a Zhuang population aged 35–74 years in Nanning - Xingxi Luo; Liling Wei; Shun Liu; Kaili Wu; Dongping Huang; Suyang Xiao; Erna Guo; Lei Lei; Xiaoqiang Qiu; Xiaoyun Zeng (Journal of Trace Elements in Medicine and Biology, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Multi-step prediction of carbon emissions based on a secondary decomposition framework coupled with stacking ensemble strategy - Boting Zhang; Liwen Ling; Liling Zeng; Huanling Hu; Dabin Zhang (Environmental Science and Pollution Research, 2023)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)